The Effect of Additional Papaya Leaf Flour on the Physical Quality of Mineral Molasses Block - Sutresna, Ersa; Wijayanti, Dwi; Kusmayadi, Andri (Bulletin of Applied Animal Research, 2026)
Mineral molasses block (MMB) is a compact feed supplement used to balance livestock mineral requirements and enhance feed efficiency. One method to improve the physical quality of MMB is by incorporating plant-based ingredients rich in bioactive compounds, such as papaya leaf powder. This study aimed to evaluate the effect of papaya leaf powder addition on the physical quality of MMB and to determine the optimal treatment level. The research was conducted using a Completely Randomized Design (CRD) with four treatments and five replications: P0 (30% molasses + 0% papaya leaf powder), P1 (25% molasses + 5% papaya leaf powder), P2 (20% molasses + 10% papaya leaf powder), and P3 (15% molasses + 15% papaya leaf powder). Observed parameters included water absorption, impact resistance, density, and organoleptic properties (color, aroma, and texture). The results showed that papaya leaf powder significantly affected water absorption, impact resistance, density, color, and texture parameters. However, it had no significant effect on MMB aroma. Increased levels of papaya leaf powder led to higher water absorption, while impact resistance, density, and organoleptic scores tended to decrease. Treatment P1 yielded the best results, with water absorption close to the control, good impact resistance and density, and the highest organoleptic scores. Keywords: Impact Resistance, MMB, Organoleptic, Papaya Leaf Powder, Water Absorption.